Karakteristik Pembakaran Briket Kokas Lokal Pada Beberapa Temperatur Karbonasi - Dedet Hermawan Setiabudi; Dwi Aries Himawanto; Sukamta Sukamta (Semesta Teknika, 2006)
In order to investigate the better carbonization process that used in foundry application, this research was performed the materials of this research are the local coke that usually used in Ceper Klaten. This local coke was pressed into cylindrical shape and then carbonize in the three variation  carbonized temperature i.e. 100 0C, 200 0C  and 300 0C as long as one hour then taken into furnace to find the combustion characteristics.The result shows that carbonization process has the optimal temperature.